2023
DOI: 10.13189/app.2023.110206
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and Nutritional Properties: Genus Salvia

Abstract: Complementary medicine has emerged with the history of humanity and has become widespread with the use of natural products in the treatment of many diseases. People have used many plant species in the treatment of diseases by benefiting from trial and error and knowledge. Plants have been used as shelter, food, medicine, spices, cosmetics, and tools for use in religious rituals. Different communities around the world have widely used local plants. In addition, the cosmopolitan species are used by all people in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…The results obtained indicated that medicinal plants are overall a significant source of mineral composition. The nutrient analysis was within the range of other reports for M. officinalis [30], S. cypria [31], and S. fruticosa [32], or had small variations, as in the cases of M. piperita [33] or T. capitatus [34]. To our knowledge, this is the first report that analyzes the mineral content and nutritional value of O. dubium.…”
Section: Mineral Content and Nutritional Valuesupporting
confidence: 80%
See 1 more Smart Citation
“…The results obtained indicated that medicinal plants are overall a significant source of mineral composition. The nutrient analysis was within the range of other reports for M. officinalis [30], S. cypria [31], and S. fruticosa [32], or had small variations, as in the cases of M. piperita [33] or T. capitatus [34]. To our knowledge, this is the first report that analyzes the mineral content and nutritional value of O. dubium.…”
Section: Mineral Content and Nutritional Valuesupporting
confidence: 80%
“…To our knowledge, this is the first report that analyzes the mineral content and nutritional value of O. dubium. Compared to other species of the Origanum genus, O. dubium appears to have a higher nutritional value than O. compactum [32].…”
Section: Mineral Content and Nutritional Valuementioning
confidence: 73%
“…Additionally, plant extractions can control the makeup of the gut microbiota by acting as anti-inflammatory medications. 4,5,6 Plants may prevent several diseases whose genesis includes immunological dysfunctions or systemic inflammation. Additionally, the bioactive components of plants can control the oxidative stress brought on by imbalanced reactive oxygen species (ROS) generation and cell enzymes' capacity to act as antioxidants.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Salvia L. is commonly known as sage and includes the most common Salvia officinalis L. (Dalmatian sage), Salvia lavandulaefolia, Salvia fruticosa, Salvia. Miltiorrhiza, and others [5], and is represented by approximately one thousand species worldwide [6,7]. Several biological activities have been reported for sage extracts, such as antibacterial, anticancer, anticholinesterase, antinociceptive, hypoglycemic, hypolipidemic, liver-protective, antioxidant, etc.…”
Section: Introductionmentioning
confidence: 99%